The Leadership Style of School Principal in Developing Religious Character of Students at Nurul Madinah Islamic Junior High School - Nurani, Budi; Fitriani, Muhammad Iwan; Hakim, Lukman (Tadbir : Jurnal Studi Manajemen Pendidikan, 2024)
This research aims to understand and evaluate the leadership style of school principals in building the religious character of students at Nurul Madinah Pelulan Islamic Middle School, Kuripan District, West Lombok Regency. Explain the religious character implemented at Nurul Madinah Pelulan Islamic Middle School, Kuripan District, West Lombok Regency. This study applies a qualitative approach by utilizing a variety of data collection methods including interviews, documentation, observation, and field surveys. Data analysis is carried out using data triangulation techniques, where researchers will carry out data reduction, data verification, and conclusion. The results of this research reveal that the leadership style of the Principal of Nurul Madinah Pelulan Islamic Middle School, Kuripan District, West Lombok Regency uses a democratic leadership style which can be seen from the process of giving awards to teachers who are dedicated and show good examples through daily practices at school to building the religious character of students. This includes the development of religious character. instilled at Nurul Madinah Islamic Middle School, including performing duha, dalail, and wirid prayers, reading and memorizing the Al-Qur'an.